METACOGNITIVE ASPECTS IN INDONESIAN LEARNING IN SENIOR HIGH SCHOOLS IN JEMBER - Alivia Nadatul Aisyi; Sarwiji Suwandi; Andayani Andayani (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2021)
Metacognition is important in learning since it is a higher order thinking process. Metacognition emphasizes on the students’ autonomy to determine the learning process which is right for them. This research was conducted on tenth grade class students in Jember. Research on three students was collected through interviews and observations. The research result was obtained in three parts, procedural, declarative, and conditional knowledge in each variable. The variables consist of self, task, and strategy. The results showed that the three metacognitive knowledge were closely related to the student learning process. The highest level in the learning process is procedural knowledge, then declarative and conditional knowledge.